Pengaruh Pengetahuan Anggota Dewan Tentang Anggaran Terhadap Pengawasan Keuangan Daerah (APBD) Dengan Variabel Moderating(Studi Empiris Pada DPRD Kabupaten Kendal) - Nugra Kencana Putra, Vidya; , Dr. ZULFIKAR SE. M.SI (2016)
ABSTRACT In research conducted to determine whether accountability, public participation, transparency of public policy, organizational commitment, and organizational culture as moderating the relationship between the knowledge of the board on the budget and financial control area (budget). This research use the quantitative method and using the primary data which get from questioner. Method for get the sample is ..... Analytic tool for this research is Moderate Analysis Regression (MRA). The results in this study is the relationship between knowledge about budgetary council affect oversight of local finance (budget). Public participation, and transparency of public policy has affect to relationship between knowledge about budgetary council affect oversight of local finance (budget). Which are accountability, organizational commitment, and organizational culture does not affect the relationship between between knowledge about budgetary council affect oversight of local finance (budget). Keyword: Accountability, Public Participation, Transparency of public policy , Organizational commitment, Organizational culture and knowledge about budgetary council affect oversight of local finance.